Graphene derivative scaffolds facilitate in vitro cell survival and maturation of dopaminergic SN4741 cells - Rodríguez-Losada, Noela; Wendelbo, Rune; García-Fernández, María Inmaculada; Pavía-Molina, José; Martinez-Montañez, Elisa; Lara-Muñoz, José Pablo; Arenas, Ernest; Aguirre-Gómez, José Ángel (My University, 2014)
The emerging carbon nanomaterial Graphene (G), in the form of scaffold structure, has an efficient bioconjugation with common biomolecules and activates cell differentiation of neuronal stem cells, providing a promising approach for neural regeneration. We propose the use of G as a scaffold to re-address the dopaminergic (DA) neurons and the residual axons from dead or apoptotic DA neurons in Parkinson´s disease (PD). G could act as a physical support to promote the axonal sprout as a “deceleration” support for the DA cells derived from neural stem cells or DA direct cell conversion, allowing the propagation of nerve impulses. We cultured a clonal substantia nigra (SN) DA neuronal progenitor cell line (SN4741) in presence of G as scaffold. This cell line derived from mouse embryos was cultured in Dulbecco’s modified Eagle’s medium/10% FCS to about 80% confluence. Cells were incubated in three chemically different G derivatives and two different presentation matrixes as powder and films: 1) G oxide (GO); 2) partially reduced GO (PRGO) which is hydrophobic; and 3) fully reduced GO (FRGO). Cell viability was determined using the MTT assay after adding the following G concentrations: 1mg/ml; 0.1mg/ml; 0.05mg/ml; 0.02mg/ml and 0.01mg/ml, in each type of GO. To study cellular morphology and assessment of cell engraftment into GO films (GO film, PRGO film, FRGO film), we analyzed the immunostaining of the anti-rabbit neuron-specific DNA-binding protein (NeuN) antibody, the anti-rat Beta-3-tubulin antibody in combination with the mitochondrial marker mouse anti-ATP synthase antibody, and the anti-rabbit DCX as immature neuronal marker. Hoechst label was used as nuclei marker. Reactive oxidative species (ROS) were measured by flow cytometry to study the influence of G on the cell redox-state. With this purpose, cells were loaded with dihydroethidium. The mitochondrial membrane potential after JC-1 incubation was studied by flow cytometry. Our results show an increase of survival and metabolism (30-40%) at low concentrations of PRGO and FRGO (0.05-0.01 mg/ml) respect to the higher concentration (1 mg/ml), while no changes were seen in the GO group. LDH concentration was measured in the supernatant using a COBAS analyzer showing a neuroprotective action at low concentrations. Furthermore, either PRGO film or FRGO film show an increase in the effective anchorage capacity to nest into the G matrix and in the maturation of the SN 4741 cells. We conclude that the use of G scaffolds in the research of neurological diseases like PD could offer a powerful platform for neural stem cells, direct cell conversion techniques and neural tissue engineering.
Keywords: Parkinson, Enfermedad de; Graphene; Stem cells; Dopaminergic; Differentiation; Parkinson's disease